2017
DOI: 10.15666/aeer/1501_079092
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Microbial Population Associated With Three Wetland Types in the Sanjiang Plain, Northeast China

Abstract: Abstract. The Sanjiang Plain is the largest freshwater wetland area in Northeast China and plays an important role in regulating climate stability for this region. However, agricultural activity has decreased wetland coverage with about 84 % since the1950s.This has resulted in lowered water tables and degraded wetlands, with dryer marsh meadows and dry meadow coverage replacing wet marshlands. Here, we report investigations towards the soil microbial community composition and diversity in the different degener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The people have realized that soil microbes are the most sensitive organisms in the soil ecological environment and are constantly explored ways to promote soil environmental remediation by controlling soil microbes (Liu et al, 2014a). In the former study, our work indicated that Acidobacteria was the most plentiful bacterial phylum in the Sanjiang plain wetland (Sui et al, 2017). The Acidobacterial numbers are most, also accounting for 20-50%, and distributed most widely in the soil, involving in plant residue matter decomposition, ferrikinetics process, single carbon compounds metabolism and some important ecological functions on the ecological environment (Wang, 2010).…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…The people have realized that soil microbes are the most sensitive organisms in the soil ecological environment and are constantly explored ways to promote soil environmental remediation by controlling soil microbes (Liu et al, 2014a). In the former study, our work indicated that Acidobacteria was the most plentiful bacterial phylum in the Sanjiang plain wetland (Sui et al, 2017). The Acidobacterial numbers are most, also accounting for 20-50%, and distributed most widely in the soil, involving in plant residue matter decomposition, ferrikinetics process, single carbon compounds metabolism and some important ecological functions on the ecological environment (Wang, 2010).…”
Section: Introductionmentioning
confidence: 67%
“…When arrived, the soils were divided into two parts: one, approximately 10 g soil was placed in a sterile microcentrifuge tube and stored in -80°C for molecular analysis; the remaining of the soils were air-dried to detect the soil physiochemical properties. These were measured as described before (Sui et al, 2017) and included the pH of the soil mixed with water (1:5 w/v); total organic carbon (TC), total nitrogen (TN) and total phosphorus (TP) content, as well as available nitrogen (AN) and available phosphorus (AP). The physiochemical properties of the soil samples from the three different land uses are summarized in Table 1.…”
Section: Site Description and Soil Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed predominance of Basidiomycota and Ascomycota was not out of expectation due to the descriptions for these groups as general inhabitants for wetland and forest soils (Han et al., 2018; Sui, 2017). In addition, Ascomycota was more frequently identified in aquatic group than dryland group, while the Basidiomycota was more frequently identified in dryland group than aquatic group.…”
Section: Discussionmentioning
confidence: 85%
“…Over the years, this phenomenon has gradually attracted attention, and researchers are focusing on studies describing the impact of wetland cultivation (Zhou et al, 2009), treatment of wetland pollution (Guo et al, 2014), or wetland microbial participation in carbon and nitrogen cycles Sui et al, 2017). It is now widely recognized that soil microbes are key players in the soil ecology.…”
Section: Introductionmentioning
confidence: 99%